Pengaruh Metode Ekspresi Bebas terhadap Kreativitas Siswa Membuat Karya Dekoratif Wayang Kulit Palembang - Sinta Maya; Robert Budi Laksana; Treny Hera (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The aim of this research is to determine the effect of the free expression method on students' creativity in creating decorative wayang kulit Palembang. The research method used in this study is an experimental method. The population in this research consisted of 31 students from class IIIA and IIIB of SD Negeri 201 Palembang in the academic year 2022/2023. Data collection techniques in this research are documentation and tests. The test data were analyzed using tests of normality, homogeneity, and hypothesis testing using the independent sample t-test. The results and discussions show that there is an influence of the free expression method on students' creativity in creating decorative wayang kulit Palembang. This can be seen from the results of the posttest scores of the experimental students who were treated using the free expression method, which is 75.6, larger than the control class which was treated using the conventional method, which is 58.43. The hypothesis testing results show that t-count is 3.358 and t-table is 2.145, which means that t-count > t-table or 3.358 > 2.145 with a significance level of 0.05, thus the null hypothesis (HO) is rejected, and the alternative hypothesis (Ha) is accepted. Therefore, in this research hypothesis, there is an effect of the free expression method on students' creativity in creating decorative wayang kulit Palembang.